Activity of natural killer cells during HIV-1 infection in Brazilian patients - Nunes, Danilo Ferreira; Carvalho, Anderson; Duarte, Alberto José da Silva (Revista do Hospital das Clínicas, 2001)
Natural killer cells are increasingly being considered an important component of innate resistance to viruses, but their role in HIV infection is controversial. Some investigators have found that natural killer cells do not confer a protective effect during the progression of HIV disease, whereas others have shown that natural killer cells may be protective and retard the progression of the disease, either through their lytic activity or by a chemokine-related suppression of HIV replication. In this study, we analyzed functional alterations in the activity of natural killer cells during HIV-1 infection using a natural killer cells activity assay with K562 cells as targets. RESULTS: Our results show that the activity of natural killer cells decreases only in the advanced phase of HIV infection and when high (40:1) effector cell-target cell ratios were used. The depression at this stage of the disease may be related to increased levels of some viral factors, such as gp120 or gag, that interfere with the binding capacity of natural killer cells, or to the decreased production of natural killer cells -activity-stimulating cytokines, such as IFN-a and IL-12, by monocytes, a subset of cells that are also affected in the late stage of HIV infection. The data suggest that decreased natural killer cells cell activity may contribute to the severe impairment of the immune system of patients in the late stages of HIV infection.